Answer:
(f - g)(x) = 3x² - 2x - 6
General Formulas and Concepts:
<u>Pre-Alg</u>
- Order of Operations: BPEMDAS
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 3x² - 2
g(x) = 2x + 4
(f - g)(x) is f(x) - g(x)
<u>Step 2: Evaluate</u>
- Substitute: (f - g)(x) = 3x² - 2 - (2x + 4)
- Distribute -1: (f - g)(x) = 3x² - 2 - 2x - 4
- Combine like terms: (f - g)(x) = 3x² - 2x - 6
The next numbers are 32 and -64 the pattern multiplies by -2
Answer:
its x^4
Step-by-step explanation:
its x^4
Distribute.
(a + 8)(a -3)
FOIL:
First, Outside, Inside, and Last
a * a = a^2
a * 3 = 3a
8 * a = 8a
8 * -3 = - 24
a^2 + 11a - 24
Distributed Expression: a^2 + 11a - 24
Answer:
f (-1) = 3
f (0) = -7
f (2) = -7
f (5) = -7
Step-by-step explanation:
f (-1) = 3
f (0) = -7
f (2) = -7
f (5) = -7